(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Reference ranges for blood and serum parameters aid in diagnosing diseases, monitoring health, and distinguishing between normal and abnormal values. There is a lack of available information and research data establishing reference ranges for haematological and serum biochemical parameters in newborn White Fulani calves. We aim to establish reference intervals for haematology and serum biochemistry analytes in apparently healthy White Fulani neonatal calves. A cross-sectional study was conducted on 30 White Fulani neonate calves under 28 days old from different farms in Ibadan, Nigeria. Blood samples were collected for haematology and serum chemistry. The haematological analysis involved packed cell volume, haemoglobin, red and white blood cell counts, differential leukocyte counts, and platelet counts using standard methods. Serum was analysed for proteins, enzymes, metabolites, electrolytes and lipid profiles using spectrophotometric techniques. Normally distributed data was analysed using 2.5th-97.5th percentiles as 95% reference intervals, with 90% confidence intervals per IFCC recommendations, using SPSS software. Haematological intervals included packed cell volume (30.11-32.29%), haemoglobin (9.26-10.04 g/dL), and white blood cell count (4.61-5.18 x 109/L) among others. Key serum biochemistry intervals were total protein (5.61-6.50 g/dL), glucose (67.12-76.78 mg/dL), cholesterol (49.98-60.52 mg/dL), creatinine (0.52-0.61 mg/dL), and electrolytes like sodium (122.25-143.95 mmol/L). The study establishes haematological and serum biochemical reference intervals for White Fulani neonate calves, suggesting their use for future research and comparisons.